Etnobotani Tumbuhan Obat oleh Suku Dayak Iban Desa Tanjung Sari Kecamatan Ketungau Tengah Kabupaten Sintang - Irwan Lovadi, Meliki, Riza Linda (Jurnal Protobiont, 2013)
This research has taken place for three months, October to December 2012, in Tanjung Sari village in Ketungau Tengah sub-district in Sintang regency. The purpose of this study is to investigate the plants used as traditional medicinal herbs by Dayak Iban (local tribe) in the vallage. The study is to find out the kinds of the plant, parts of the plants and the process of making them into medicine. Snowball method is used to collect as well as to identify the kinds of the plants used by the tribe. The study shows that there are 65 (sixty five) kinds of medicinal herbs coming from 38 (thirty eight) families. Many are from the family of Zingiberaceae (12.3 %), Euphorbiaceae (7.6 %) and Poaceae and most of them are taken from the forest. The tribe uses mainly leaves as the herbs. Most of the herbs can be found the forest. The herbs are able to cure 38 (thirty eight) diseases.